2017
DOI: 10.1016/j.neuron.2016.11.019
|View full text |Cite
|
Sign up to set email alerts
|

BK Channels Are Required for Multisensory Plasticity in the Oculomotor System

Abstract: SUMMARY Neural circuits are endowed with several forms of intrinsic and synaptic plasticity that could contribute to adaptive changes in behavior, but circuit complexities have hindered linking specific cellular mechanisms with their behavioral consequences. Eye movements generated by simple brainstem circuits provide a means for relating cellular plasticity to behavioral gain control. Here we show that firing rate potentiation, a form of intrinsic plasticity mediated by reductions in BK-type calcium activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…It should be noted that in contrast to pyramidal cells that are silent at rest, these cells correspond to pacemaker neurons that continuously fire at 5-10 Hz. Interestingly, vestibular sensory loss triggers rapid potentiation of excitability in vestibular neurons thus enabling adaptive compensatory increases in optokinetic reflex gain [67 ].…”
Section: Homeostatic Plasticity Of Iementioning
confidence: 99%
“…It should be noted that in contrast to pyramidal cells that are silent at rest, these cells correspond to pacemaker neurons that continuously fire at 5-10 Hz. Interestingly, vestibular sensory loss triggers rapid potentiation of excitability in vestibular neurons thus enabling adaptive compensatory increases in optokinetic reflex gain [67 ].…”
Section: Homeostatic Plasticity Of Iementioning
confidence: 99%
“…Key organ and functional systems disrupted by BK channel dysfunction in mouse models are indicated. BK channel activity was required for several aspects of neurological operations in rodent models, such as regulation of neuronal excitability (Jin et al, 2000;Faber and Sah, 2003;Brenner et al, 2005;Shruti et al, 2008;Sheehan et al, 2009), locomotor function (Meredith et al, 2004;Sausbier et al, 2004;Chen et al, 2010), circadian rhythm Kent and Meredith, 2008;Montgomery et al, 2013;White et al, 2015;Whitt et al, 2016), learning and memory (Typlt et al, 2013b), vision (Henne and Jeserich, 2004;Grimes et al, 2009;Tanimoto et al, 2012), hearing and vestibular reflexes (Pyott et al, 2007;Maison et al, 2013;Rohmann et al, 2015;Pyott and Duncan, 2016;Nelson et al, 2017), and neurovascular coupling (Filosa et al, 2006;Girouard et al, 2010). In addition to neurological roles, rodent models further revealed that BK channels are required for regulation of cardiovascular function (Sausbier et al, 2005;Imlach et al, 2010;Lai et al, 2014;Nagaraj et al, 2016), airway control Goldklang et al, 2013;Manzanares et al, 2014), urination (Meredith et al, 2004;Thorneloe et al, 2005;Brown et al, 2008;Sprossmann et al, 2009), glucose homeostasis (Houamed et al, 2010;Düfer et al, 2011), renal K + homeostasis…”
Section: Neuronal Mechanisms Of Bk Channel Dysfunctionmentioning
confidence: 99%
“…Data on expression levels were derived from the Human Protein Atlas v18.1 (https://www.proteinatlas.org) (Uhlén et al, 2015), the NCBI Gene Database (https://www.ncbi.nlm.nih.gov), and published reports (Dworetzky et al, 1994;McCobb et al, 1995;Brenner et al, 2000). (Jin et al, 2000;Faber and Sah, 2003;Brenner et al, 2005;Shruti et al, 2008;Sheehan et al, 2009), locomotor function (Meredith et al, 2004;Sausbier et al, 2004;Chen et al, 2010), circadian rhythm (Meredith et al, 2006;Kent and Meredith, 2008;Montgomery et al, 2013;White et al, 2014;Whitt et al, 2016), learning and memory (Typlt et al, 2013b), vision (Henne and Jeserich, 2004;Grimes et al, 2009;Tanimoto et al, 2012), hearing and vestibular reflexes (Pyott et al, 2007;Maison et al, 2013;Rohmann et al, 2015;Pyott and Duncan, 2016;Nelson et al, 2017), and neurovascular coupling (Filosa et al, 2006;Girouard et al, 2010). In addition to neurological roles, rodent models further revealed that BK channels are required for regulation of cardiovascular function (Sausbier et al, 2005;Imlach et al, 2010;Lai et al, 2014;Nagaraj et al, 2016), airway control (Sausbier et al, 2007;Goldklang et al, 2013;Manzanares et al, 2014), urination…”
Section: Precision Medicine and Future Directionsmentioning
confidence: 99%